More tractable average error rate expression for the Nth best relay selection scheme of DF relaying over Rayleigh fading channels. (12th January 2012) - Ko, K.; Woo, C.
SUMMARY In this paper, we derive another exact average error rate expression for the Nth best decode‐and‐forward relay systems over Rayleigh fading channels. On the basis of error‐events at relay nodes, the Nth best relay's selection probability is expressed as a more tractable form in which the number of summations and the length of each summation are specified. Then, exact average error performance metrics are obtained as two well‐known forms. The first is expressed with a moment generating function, and the other is presented as a closed form. Simulation results are finally presented to validate that the derived analytical expression can be a general frame work covering all Rayleigh fading channel conditions. Copyright © 2012 John Wiley & Sons, Ltd.